The value of determination of serum myoglobin in estimation of degree of illness and prognosis of patients with sepsis in Xining area - Liu, Mei (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2011)
OBJECTIVE: To investigate the value of determination of serum myoglobin (MYO) in estimation of the degree of illness and prognosis of patients with sepsis in Xining area